Expression Profiling in Bemisia tabaci under Insecticide Treatment: Indicating the Necessity for Custom Reference Gene Selection - Liang, Pei; Guo, Yajie; Zhou, Xuguo; Gao, Xiwu (PloS one, 2014)
Finding a suitable reference gene is the key for qRT-PCR analysis. However, none of the reference gene discovered thus far can be utilized universally under various biotic and abiotic experimental conditions. In this study, we further examine the stability of candidate reference genes under a single abiotic factor, insecticide treatment. After being exposed to eight commercially available insecticides, which belong to five different classes, the expression profiles of eight housekeeping genes in the sweetpotato whitefly, Bemisia tabaci, one of the most invasive and destructive pests in the world, were investigated using qRT-PCR analysis. In summary, elongation factor 1α (EF1α), α-tubulin (TUB1α) and glyceraldehyde-3-phosphate dehydrogenase (GAPDH) were identified as the most stable reference genes under the insecticide treatment. The initial assessment of candidate reference genes was further validated with the expression of two target genes, a P450 (Cyp6cm1) and a glutathione S-transferase (GST). However, ranking of reference genes varied substantially among intra- and inter-classes of insecticides. These combined data strongly suggested the necessity of conducting custom reference gene selection designed for each and every experimental condition, even when examining the same abiotic or biotic factor.